Fade into you: genetic control of pigmentation patterns in red-flesh apple (Malus domestica) - Bouillon, Pierre; Belin, Etienne; Fanciullino, Anne-Laure; Balzergue, Sandrine; Hanteville, Sylvain; Letekoma, Yao; Cournol, Maryline; Faris, Fatima; Bouanich, Andréa; Bréard, Dimitri; Bernard, Frédéric; Celton, Jean-Marc (Frontiers in Plant Science, 2025)
The genetic basis of type 1 red-flesh color development in apple (Malus domestica) depends upon a particular allele of the MdMYB10 gene. Interestingly, type 1 red-flesh apples are fully red after fruit set, but anthocyanin pigmentation in apple fruit cortex may decrease during fruit growth and maturation, leading to variable red patterning and intensities in the mature cortical flesh. We developed a histogram-based color analysis method to quantitatively estimate pigmentation patterns. This methodology was applied to investigate the phenotypic diversity in four hybrid F1 families segregating for red-flesh color. Pigmentation patterns were found to be heritable allowing the identification of a new locus by QTL analysis. To further investigate the mechanisms involved in the spatial deposition of anthocyanin, metabolome, transcriptome and methylome comparisons between white and red flesh areas within the red-flesh genotype cv. ‘R201’ exhibiting flesh pigmentation patterns, was performed. Wide-targeted analysis showed that white-flesh areas accumulate more dihydrochalcones and hydroxycinnamic acids than red-flesh areas while red-flesh areas accumulate more flavonoids. Anthocyanin biosynthesis genes and anthocyanin positive regulators (MBW complex) were up-regulated in red-flesh areas, while a reduction in anthocyanin storage, transport and stability (increase of pH, down-regulation of MdGSTU22) and an increase in phenolic catabolism were concomitant with color fading process in white-flesh areas. Expression of MdGSTU22 was linked to a differentially methylated region (DMR) suggesting a potential environmental effect on the epigenetic control of gene expression involved in color fading. Altogether, these results provide the first characterization and functional identification of color fading in apple fruit flesh.